A dissipative constitutive model for woven composite fabric under large strain. (February 2018) - Denis, Y.; Guzman-Maldonado, E.; Hamila, N.; Colmars, J.; Morestin, F.
Abstract: Draping composite reinforcement on non-developable shapes necessarily leads to deformations in the plane generating large shears between warp and weft. Sliding between fibers and between yarns creates friction that dissipates energy. This paper presents a constitutive model describing the dissipative behaviour of 2D composite textile reinforcements under large strain. The model is based on two innovative points. First, the additive decomposition of Green-Naghdi is considered, which leads to write the yield function and the plastic law in a conventional manner, which is very uncommon for anisotropic fields. Secondly, nested surfaces according with Mroz Theory define the strong non-linearity of the problem. The use of these two points allows to define a flexible dissipative model for numerical simulations. The dissipation process driven by fibers friction is exclusively associated with the in-plane shear deformation mode. As a result, the material parameters are calibrated using standard methods, like the Picture Frame.